International business acquisitions : (Sold and distributed in the USA and Canada by Aspen Pub,Kluwer Law International, 2007)
Third Edition include the following: new contributions from China, Finland, Israel, Luxembourg, Austria, and Argentina, making a total of 35 jurisdictions; effects of the spectacular growth of private equity investment vehicles as major players in the international mergers and acquisitions space; effects of the increasing impact of European Union regulations and directives on corporate transactions; effects of the increasing sophistication and even harmonisation in competition (antitrust) laws.